PENEGAKAN HUKUM PIDANA PERIKANAN DI INDONESIA STUDI KASUS PENGADILAN NEGERI MEDAN - Maria Maya Lestari (Jurnal Ilmu Hukum, 2013)
Recognition of the legal regime ofthe sea on the concept of islandstates automatically grant us therights and obligations of all naturalresources, especially fisheries thatexist both in the territorial sea up tothe exclusive economic zone. But inlaw enforcement, having not onlythe weakness of the differentterminology goods / and or theevidence seized goods that willcreate turmoil in the process ofproving before trial. Beside that thelanguage issue is also gettingattention in the practice fieldwhere, in some cases, the suspectswere there who could not speakEnglish let alone speak Indonesian.Kata Kunci : Peradilan perikanan, Hukum Laut